Pola Makan pada Penderita Hipertensi di Puskesmas Tuban, Kabupaten Tuban - Herlambang, Yoga Septian; Nugraheni, Wahyuningsih Triana; Ningsih, Wahyu Tri (Journal of Health Management Research, 2024)
Background: Hypertension, also known as high blood pressure, is a non-communicable disease which is one of the leading causes of death in the world. WHO data shows that hypertension is still a major health problem. At this time people still often consume foods that cause hypertension and diet is one of the main modifiable risk factors for hypertension. Aims: The purpose of this research is to know the eating patterns of hypertension sufferers at the Tuban Health Center. Methods: The design of this study was descriptive. The study population was all hypertensive patients who took part in the Prolanis program at the Tuban Health Center, totaling 64 patients. The sample size is 64 patients. Using Total Sampling technique. Retrieval of data with a questionnaire. Data were analyzed descriptively with frequency tables. Results: The results showed that the most hypertension sufferers at the Tuban Health Center were aged 56-65 years (40.6%). Most people with hypertension have secondary education (37.5%). And most of them don't work (54.6%). Most of the eating patterns in people with hypertension are lacking (58%). Most of the hypertensive patients aged >65 years had a good diet (71%), almost all of the highly educated hypertensive patients had a poor diet (76%), and most of the unemployed hypertensive patients had a moderate diet. less category (60%). Conclusion: Increasing age makes a person more concerned with eating patterns, the level of education also does not make someone maintain eating patterns, someone who does not work tends not to maintain diets.